2021
DOI: 10.1186/s42077-021-00144-8
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone to decrease post-anesthesia sore throat (POST) and hoarseness-which is the most effective route: intravenous, topical, or nebulization? A prospective randomized trial

Abstract: Background and Aims Postoperative sore throat (POST) is common after endotracheal intubation making patients uncomfortable and anxious in postoperative period. The present study was undertaken to compare efficacy of equal dose of dexamethasone in preventing POST via three different routes, i.e., intravenous, topical, and nebulization before surgery. Methods and Results The present prospective double-blind randomized parallel group trial included 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, many prior studies have shown that the incidence of POST may be up to 70% and that of hoarseness is reported to range from 4-43%. [1][2][3][4] Even though the incidence of POST and hoarseness of voice was lower in the fluticasone group than in the control group in this study, there was never a postoperative difference that was statistically significant. This study is comparable to one by Park SY et al, 37 which compared the incidence of POST in patients with tracheal tubes impregnated with triamcinolone acetonide (n=72) and chlorhexidine (n=72) during intubation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, many prior studies have shown that the incidence of POST may be up to 70% and that of hoarseness is reported to range from 4-43%. [1][2][3][4] Even though the incidence of POST and hoarseness of voice was lower in the fluticasone group than in the control group in this study, there was never a postoperative difference that was statistically significant. This study is comparable to one by Park SY et al, 37 which compared the incidence of POST in patients with tracheal tubes impregnated with triamcinolone acetonide (n=72) and chlorhexidine (n=72) during intubation.…”
Section: Discussionmentioning
confidence: 55%
“…Postoperative sore throat (POST), which ranges from 12.1% to 70%, is one of the commonest consequences of intubation, while hoarseness of voice varies from 4-43%. [1][2][3] The eighth worst possible post-anesthesia effect is POST, which imparts a strongly negative influence on the overall experience of surgery and stay in the hospital postoperatively. 4 POST is caused by a number of different factors, including vocal cord damage, congestive blood loss, and damage to the epithelium and mucosal cells caused by airway secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Topical dexamethasone has been found to be as effective as intravenous dexamethasone; however, nebulization has been found to be the most effective technique. [ 36 ]…”
Section: Role Of Dexamethasone In Postoperative Sore Throatmentioning
confidence: 99%
“…The endotracheal tube is very much crucial to achieve the airway control during GA. [1] Despite rapid advancement in anesthetic techniques, [2] throat complications for example, sore throat and hoarseness after surgery are common complications of GA with tracheal intubation. [3,4] The POST (postoperative sore throat) causes cough while cough after surgery leads to stress at stitch site that increases the pain at operation site [5] and hence further boosts the patient's dissatisfaction and discomfort. Also, it adds to the patient morbidity and can affect patient's activities after leaving the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The POST incidence could be <90% and that of the hoarseness described in different researches ranges from 4-43 percent. [5] The sore throat etiology is still not known clearly [8] however it seems to be an inflaming process since tracheal mucosa was found to exude inflaming mediators after the intubation. [9,10] Several influencing factors have been recognized while the most significant one appears to be ETT size utilized, anesthetic spray usage, cuff pressure, female gender, anesthesia duration, succinylcholine usage, surgical positioning, simultaneous usage of the nasogastric tube, oropharyngeal aggressive suctioning and technique to manage the airway (i.e.…”
Section: Introductionmentioning
confidence: 99%